Developing Network Security in Small and Medium-sized SaaS Industry Enterprise - Kemppinen, Edgar (My University, 2019)
Network security’s mission is to secure data and hosts in a network environment by ensuring confidentiality, integrity, non-repudiation, availability, access control, and authentication. A Software as a Service (SaaS) industry enterprise has developers in their network so that it may contain servers and services, but it also requires stability for comfortable work. Small and medium-sized enterprise (SME) sets budget to network gear and security measures that the enterprise can afford to maintain a secure network environment. This thesis presents solutions for network threats and how they can be analyzed in a SaaS industry SME. Used references are from scientific articles and web resources. Implementable and relevant solution for the found threat is discussed. The implementation is analyzed for new threats to see how it would affect the production environment. The enterprise can have issues with network access, internal security, and network stability. Wireless connections may use weak encryption protocols. Inside the network, the attacker can launch various attacks. Network stability can be weakened inside and outside of the target network. Firewalls and intrusion detections systems (IDS) or intrusion prevention systems (IPS) can be used to improve the security of the network environment, but they require the right settings and maintenance. Threats of the network can be identified using the STRIDE model, and they can be rated using the DREAD model. It was discovered that the analyzed target network has many issues. The most important in the sense of priority is related to access control. Implementation of WPA2-Enterprise will fix wireless access control issues, but a wrong implementation and weak user passwords will bring new issues.